The Expiration of Exigence : How Postmodern Frameworks Dissolve and What Rhetoric Can Do About It. - Schlechty, Anastasia (Columbia Undergraduate Research Journal, 2020)
Lloyd Bitzer’s 1968 article, “The Rhetorical Situation,” reframed scholarship on communication. Prior to this, rhetorical studies primarily looked to content and style of discourse in order to provide an analysis of meaning and value; however, scholars became frustrated with the limited access that this type of framework afforded. The 1960s marked a dramatic shift in dominant rhetorical thinking from modern thought toward a realm of new ideological approaches, including postmodern thought. Environment became a major focus of postmodern communication studies, claiming that the situation, more than the content itself, determines the message. Rhetorical frameworks continue to rely on a modern or postmodern consciousness, despite the emergence of yet another societal shift into an evolved postmodernism, a reaction to the biases inherent in this relativism. Specifically, the evolution of the postmodern mind into an apathetic consciousness leads to an expiration of exigency as Bitzer defined it 50 years ago. This paper argues that current scholarship lacks a complete awareness of these new assumptions and understandings, specifically relating to cultural apathy. This paper will recount the historical context that leads into this modern framework, illustrate the situation, and argue the potential solutions. Ultimately, this paper reveals that much exigency inhabits a devalued position in the now-evolved postmodern mind, and rhetorical theory must renovate its understanding on discourse accordingly through three steps: acknowledgment, updated definitions, and thoughtful discourse.